The Effectiveness of Using POM-QM For Windows 3 Software in the STAD Type Cooperative Model in Mathematics Learning for Grade XI at SMA Negeri 9 Gowa - Alamsyah, Muhammad Nur (INTELEKTIUM, 2024)
The Effectiveness of Using POM-QM For Windows 3 in Cooperative Model Type STAD on Mathematics Learning at Grade XI IPA 3 SMA Negeri 9 Gowa. Thesis. Mathematics and Science Faculty. State University of Makassar. Advisers: Prof. Suradi, MS, and Dr. Muhammad Darwis, M.Pd. This research was Pre Experiment Research, which aimed to find out the effectiveness of using software POM-QM For Windows 3 in cooperative model type STAD on learning mathematics at grade XI IPA SMA Negeri 9 Gowa. Experimental unit in this study consisted of students in grade XI IPA 3 SMA Negeri 9 Gowa to be given preferential treatment in the form of learning by using software POM-QM For Windows 3. The sample in this research was the class XI IPA 3 that consists of 35 students with material was linear programming. This research was carried out during the 6 meeting that consists of 1 meeting of the pretest, 1 meeting of the posttest and 4 meeting of the preferential treatment in the form of learning by using software POM-QM For Windows 3 in learning mathematics. Data retrieval was performed using sheet of observations, the learning achievement test and student response questionnaire. The data were analyzed using descriptive and inferential statistical analysis. Results achieved after using the software POM-QM For Windows 3 in mathematical learning, with the content linear programming were: (1) the mean of student learning achievement test is of as ideal score; (2) Student classical exhaustiveness is ; (3) the mean value of the normalized gain is in the high category; (4) Mean score of student posttest learning achievement is significantly less than ; (5) Mean of student learning achievement improvement is significantly greater than ; (6) the mean of student learning activity is or is the active category; (7) the mean score of student response is in tend to be positive category; (8) The indicator score (criteria) general effectiveness is with quite effective category. In general it can be concluded that the application of learning by using software POM-QM For Windows 3 in cooperative model type STAD on learning mathematics is effective for use in students of grade XI IPA 3 SMA Negeri 9 Gowa according to learning achievement, student activity and student response to content linear programming because be quite effective category.